2017
DOI: 10.11604/pamj.2017.27.13.10623
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of problem-based learning curriculum implementation in a clerkship rotation of a newly established African medical training institution: lessons from the University of Botswana

Abstract: IntroductionProblem-based Learning (PBL) curricula, like all curricula, require systematic evaluation as there is a risk of implementing a dysfunctional PBL curriculum. The study intended to evaluate the PBL curriculum delivery from the perspective of the clerkship students at the University of Botswana-Faculty of Medicine.MethodsA cross-sectional study was conducted among clerkship students in Family Medicine, Paediatrics, Internal Medicine and Surgery. During a 4-week period, each respondent completed weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…PBL is acknowledged as a powerful strategy supporting higher-order cognitive processes among the members of the group (Donner and Bickley, 1993). Knowledge application and diagnostic reasoning skills are acquired through given cases to address a variety of clinical problems ( Tshitenge, Ndhlovu and Ogundipe, 2017 ). Students develop better clinical reasoning skills, use time efficiently, and retain clinical knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…PBL is acknowledged as a powerful strategy supporting higher-order cognitive processes among the members of the group (Donner and Bickley, 1993). Knowledge application and diagnostic reasoning skills are acquired through given cases to address a variety of clinical problems ( Tshitenge, Ndhlovu and Ogundipe, 2017 ). Students develop better clinical reasoning skills, use time efficiently, and retain clinical knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…Для вирішення різноманітних клінічних проблем застосовуються попередньо набуті знання і навички, при цьому поліпшується діагностичне міркування на основі аналізу конкретних випадків. У здобувачів вищої освіти розвиваються навички клінічного мислення, вони ефективно використовують час і активно здобувають клінічні знання [13]. Позитивний ефект від проблемного навчання повністю залежить від ефективної співпраці між здобувачем вищої освіти і викладачем за допомогою міжпрофесійного підходу, який зосереджений на командній роботі та гарантованій професійній ідентичності, формуючи тим самим професійне зростання.…”
Section: медична освітаunclassified
“…The most frequent methodology were surveys or questionnaires (29 studies) followed by comparative studies with traditional or lecture-based methodology (19 studies, 7 of them were randomized). Almost all the studies (47) have shown that PBL is generally well-received (Sokas et al 1990;Blosser & Jones 1991;Usherwood 1991;Bernstein et al 1995;Kaufman & Mann 1996;Kalaian & Mullan 1996;Gresham & Philp 1996;Vincelette 1997;Kaufman & Mann 1999;Antepohl & Herzig 1999;Casassus et al 1999;Purdy et al 1999;Farrell et al 1999;Ghosh & Dawka 2000;Dyke et al 2001;Walters 2001;Leung et al 2001;Khoo et al 2001;Villamor 2001;Curtis et al 2001;Trevena & Clarke 2002;Chang et al 2004;McLean 2004;Casey et al 2005;Abu-Hijleh et al 2005;Lucas et al 2006;Burgun et al 2006;Gurpinar et al 2009;Suleman et al 2010;Wang et al 2010;Tian et al 2012;Elzubeir 2012;Sulaiman & Hamdy 2013;Albarrak et al 2013;Li et al 2013;Meo 2014;Khoshnevisasl et al 2014;Nosair et al 2015;González et al 2015;Tshitenge et al 2017;…”
Section: Student Satisfactionmentioning
confidence: 99%